Kualitas Produk, Lokasi, Dan Brand Image Sebagai Determinan Kepuasan Pelanggan Pada UMKM Berwish Coffee Bandar Lampung - Prasetiyo, Angga; Warganegara, Tri Lestira Putri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Siliwangi, 2025)
This study examines the determinants of customer satisfaction at Brewish Coffee, a local coffee shop MSME in Bandar Lampung, with a focus on product quality, location, and brand image. Despite the growing coffee shop industry in Indonesia, limited empirical studies have addressed how these three factors simultaneously shape customer satisfaction in local MSMEs, particularly in non-metropolitan cities such as Bandar Lampung. Using a quantitative associative approach, data were collected through questionnaires distributed to 100 respondents selected via the Slovin formula from a population of 37,400 customers. Multiple linear regression analysis was employed to test the hypotheses. The results show that location has a significant positive effect on customer satisfaction (p = 0.000), while product quality (p = 0.502) and brand image (p = 0.904) do not show significant partial effects. However, simultaneously, all three variables significantly influence customer satisfaction (p = 0.000), with an Adjusted R2 of 0.957. This study contributes empirical evidence on the dominant role of location in determining satisfaction within the local coffee shop context and offers practical implications for MSME operators in strengthening their competitive strategy.